Faktor Internal Dan Eksternal Perbankan Pada Non Performing Loan (NPL) Dengan Inflasi Sebagai Variabel Moderasi - Debora Cornelia Antang; Yohanes Joni Pambelum; Muhammad Ichsan Diarsyad; Lamria Simamora; Rapel Rapel; Tatik Zulaika (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to analyze internal and external banking factors that can affect Non-Performing Loans (NPL) at state-owned commercial banks listed on the Indonesia Stock Exchange for the 2017-2022 period by using inflation as a moderating variable. This research method is quantitative research using secondary data in the form of financial reports. The population of this study is BUMN Commercial Banks for the 2017-2020 period with a total sample of 96 using the purposive sampling method. The data analysis technique is multiple linear regression analysis and Moderated Regression Analysis (MRA) using the SPSS 25 program.The results of this study indicate that BOPO has a positive and significant effect on NPL, and the BI rate has a negative and significant effect on NPL. Meanwhile, CAR and LDR have no significant effect on NPL. Inflation is able to strengthen LDR against NPL, inflation is unable to strengthen CAR and BI rate against NPL and weakens BOPO against NPL. State-owned banks must manage their operational activities properly and must be selective in choosing customers who receive credit so that NPL spikes can be minimized. Then, for future researchers it is hoped that they can add other variables outside of this study.